FEASIBILITY STUDY OF OZONE GENERATOR BASED ON HIGH VOLTAGE ELECTRODE METHOD - Saiful Hidayat Hizbullah; Eko Krisdiono; Priyadi Hartoko (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2021)
Currently, various technologies are being developed which aim to improve the oxidation process so that its pollutant byproducts can be reduced. One of them is the development of the use of ozone as an alternative oxidizer which in the organic chemistry perspective has more free electrons so it is more reactive than oxygen. Ozone can be produced through several methods, such as the electrolysis method, the incandescent electrode method and the high voltage electrode method. This study aims to measure the feasibility of an ozone-producing reactor based on the high-voltage electrode method to produce photon strips initiating the formation of oxygen radicals. As the main indicators of the feasibility is the efficiency and level of performance of the reactor in producing ozone. As a comparison, the reactor is based on the previously made incandescent electrode method. Based on data from experimental results in the laboratory it can be shown that the high voltage method reactor is quite feasible. It can be proven in the discussion and analysis using linear regression and Minitab software that this method provides an increase in efficiency of 0.5% (0.714% to 1.214%) and an increase in performance of 1.8 ppm / min (2.57 ppm / min to 4, 37 ppm / minute ozone gas can be produced from 2.4 L / min of atmospheric air flowed into the reactor tube). Keywords: Laboratory Experiment, Application, ASTM D-2912, Linear Regression and Minitab Software, Product Feasibility.